THE ANALYSIS OF INTEREST IN WRITING POETRY TEXT OF X GRADER STUDENTS OF VOCATIONAL HIGH SCHOOL STUDENT - Rizki Dwi Heryadi; Enung Nurhayati (JLER (Journal of Language Education Research), 2022)
This research was made to find out how interested students are in writing poetry texts and some factors that cause them. The research method which used in this research is descriptive qualitative with the type of research in the form of field research (field research). The research was conducted at SMK 2 Pacet from April 8th to 16th 2021 with numbers of samples as much as 38 people. From this study, the writer found that only about 10.8% of students expressed interest in literature, especially poetry while 83.8% of other students stated that they were not as that interested to poetry because poetry and about 6% of other students stated that they were not interested. From the research data, it can be concluded that students' interest in poetry writing activities is still under expectation.